Afro-Indigenous Cosmographies of Mobility: Fishes, Viruses and Others Amazonian Lives at the Confluence With the Sars-CoV-19 - Baines, Stephen Grant; de Castro Pereira, Márcia Leila; dos Santos, Potyguara Alencar (Frontiers in Sociology, 2021)
The article aims to demonstrate the susceptibility to death that certain Amazonian peoples are facing, as a consequence of their particular migratory demography, which instead of being curbed, have been exponentially intensified by the outbreak of Sars-CoV-19. The article offers an account of the “pendular migrations” and “return migrations” that the indigenous and black rural populations of that region carry out as a result of daily labor displacements, in the search for medical-hospital assistance and the consolidation of political and legal visibility within the cities. In a second effort, directly related to the previous one, we articulate the interference of the viral threat not on the contingency of population flow, but on the dangerous intensification of people circulation between the territorial nuclei of the “first habitation” and the average Amazonian cities, where, as a rule, these peoples maintain "second residences" and to where they regularly transmigrate. To illustrate this phenomenon, three accounts of different Brazilian Amazonian realities are reported: on the rural black population of the banks of the Turiaçu River, Maranhão state, the indigenous people of the savannah Lavrado, of the northeast of Roraima state, and the Mura people, who live in the southeast region of Amazonas state. On these realities, the cosmographies of the mobility of their populations are challenged by the changes and strategic conditions imposed by the pandemic.